Mixed Governance Principles in the Gulf Lowlands of Mesoamerica - Stark, Barbara L.; Stoner, Wesley D. (Frontiers in Political Science, 2022)
With antecedents reaching back to the Olmec era 1500-600 BC, complex societies from AD 300-900/1000 in the Gulf lowlands display architectural and material culture indications of both authoritarian and collective governance principles over two large areas, each with a distinctive version of a common architectural layout. The two areas include multiple polities adhering to particular layouts of structures providing key urban services. Our information derives from pedestrian surveys and mapping covering about 5000 sq km, plus remote sensing over 53,000 sq km. Remote sensing reveals the extraordinary extent and consistency of the predominant architectural patterns. Starting with the Olmec era and continuing into the AD 300-600 interval some sculpture glorifies individual rulers, but, at the same time, architecture shows the importance of corporate groups and public access to services that represent a more collective emphasis. Throughout the AD 300-900 span, massive platforms that supported palatial residences indicate powerful elites and rulers. Long mounds located on each side of the main plazas likely supported multiple rooms used by corporate civic groups. In some centers, multiple plaza groups attest to division of authority across several segments, and as do chains of plazas in other cases. Thus, both authoritarian and collective principles are built into the design of urban centers. The spatial extent of the dominant patterns suggests open networks of interaction consonant with low-density urbanism in the tropics. We concentrate our discussion of governance on south-central Veracruz during AD 300-900, for which we have more complete data, and we more briefly characterize the larger temporal and spatial framework. In south-central Veracruz, internal production of wealth (e.g., cotton and textiles for export) likely contributed to the long-standing strength of collective action, in keeping with a cross-cultural study of governance. Eventually the tradition in culture and governance collapsed. The demise of these urban networks was complex, but one ingredient may have been increasing disparities in wealth and corrosion of collective action.